Physical seed dormancy in pea is genetically separable from seed coat thickness and roughness - Williams, Owen R.; Vander Schoor, Jacqueline K.; Butler, Jakob B.; Hecht, Valérie F. G.; Weller, James L. (Frontiers in Plant Science, 2024)
The seeds of wild pea (Pisum) have marked physical dormancy due to impermeability to water, and the loss of this dormancy is arguably the most important trait for domestication. Seed coats of wild pea also exhibit notably thick and rough testaboth traits that have also reduced during domestication and are anecdotally linked to increased permeability. However, how these traits specifically interact with permeability is unclear. To investigate this, we examined the genetic control of differences in seed coat characteristics between wild P. sativum ssp. humile and a non-dormant domesticated P. s. sativum accession in a recombinant inbred population. In the seed of this population we found a moderate correlation between testa thickness and permeability, and identified loci that affect them independently, suggesting no close functional association. However, the major loci affecting both testa thickness and permeability collocated closely with the pigmentation loci Mendel's A, suggesting flavonoid compounds under its control might contribute significantly to both traits, a possibility that warrants further study. We also show that seed coat roughness is polygenic in this population, with the major locus independent of both testa thickness and permeability, suggesting selection for smooth seed was unlikely to be due to effects on either of these traits.